Hyperelastic Mg-Sc-based shape memory alloy and preparation method and application thereof
Through high-temperature closed smelting method and rare earth doping technology, combined with hot extrusion and cyclic heat treatment technology, the strength and super elastic properties of Mg-Sc alloy are improved, and the problems of high density and cost of lightweight shape memory alloys are solved. It is suitable for multiple Domain application.
Patent Information
- Application Number
- CN202411350485.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing lightweight shape memory alloys have shortcomings in density and ultra-elastic properties, and are relatively expensive to meet the needs of aerospace and other fields.
The Mg-Sc-based alloy is prepared by high-temperature sealed smelting method, and the strength and superelastic properties of the alloy are improved and the production cost is reduced through the doping and hot extrusion of the rare earth element Gd, cold rolling, and cyclic heat treatment processes.
The density reduction, ultra-elastic performance improvement and cost control of Mg-Sc alloys are achieved, and are suitable for aerospace, biomedical and automotive engineering fields.
Smart Images

Figure CN119220837A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of shape memory alloys, and in particular relates to a superelastic Mg-Sc based shape memory alloy and a preparation method and application thereof. Background Art
[0002] With the growing demand for low energy consumption in the aerospace, automotive and other fields, lightweight smart materials have become a research focus. Shape memory alloys, as a typical smart material, are widely used in aerospace, biomedicine, artificial intelligence, automotive engineering and other fields, but their average density is between 6 and 9 g / cm 3 , which cannot meet the demand for lightweight. Although the researchers have reduced the density to a certain extent by preparing porous shape memory alloys, there are still problems such as low strength and poor mechanical properties. By replacing the heavy elements in traditional NiTi alloys with lightweight elements, NiAl-based shape memory alloys and β-Ti-based shape memory alloys were formed. However, the processing performance of NiAl-based alloys is poor, and although the density of β-Ti-based alloys has been reduced, the density still reaches 4.5g / cm 3 Therefore, it is urgent to find a new type of lightweight shape memory alloy in order to fundamentally solve the problem.
[0003] Magnesium-Sc alloy is a Mg-rare earth alloy with BCC structure in a relatively high temperature range. Within a certain composition range, Mg-Sc alloy has shape memory effect and superelasticity. It is the only lightweight magnesium-based shape memory alloy discovered so far. The density of Mg-Sc alloy is about 2g / cm 3 , whose density is one-third of that of NiTi shape memory alloy, is expected to become a new type of lightweight shape memory alloy to meet the growing demand for lightweight functional materials in driving and sensing products. However, the phase transition temperature of Mg-Sc binary alloy is low, the superelasticity is poor, and the cost of Sc is high, which limits its application in aerospace and other fields. Therefore, it is particularly necessary to improve the superelasticity of Mg-Sc binary alloy and solve the problem of its high production cost. Summary of the invention
[0004] In order to overcome the above technical problems, the present invention provides a superelastic Mg-Sc based shape memory alloy and a preparation method and application thereof.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide a method for preparing a superelastic Mg-Sc based shape memory alloy, the method being carried out according to the following steps:
[0007] S1: According to Mg-xat.%Sc-yat.%Gd, x=17-22, y=1-2, weigh pure magnesium, pure scandium and Mg-Gd master alloy;
[0008] S2: Put the raw materials into the stainless steel crucible in order, and pass SF 6 and CO 2 After the air in the crucible is driven out by the mixed gas, the smelting is carried out in stages under high temperature and closed conditions, and an ingot is obtained after cooling;
[0009] S3: homogenizing the ingot;
[0010] S4: After homogenization treatment, the ingot is first hot extruded, then cold rolled, and finally cyclically heat treated to obtain a superelastic Mg-Sc based shape memory alloy.
[0011] It is further defined that the raw materials in the S2 crucible are, from the bottom to the top, 1 / 3 pure magnesium, 1 / 3 pure scandium, 1 / 2 intermediate alloy, 1 / 3 pure scandium, 1 / 3 pure magnesium, 1 / 3 pure scandium, 1 / 2 intermediate alloy, and 1 / 3 pure magnesium.
[0012] It is further defined that the smelting in S2 is divided into three stages: the first stage: heating to 800-850°C at a rate of 15-20°C / min, and keeping warm for 60-90min; the second stage: heating to 1000-1050°C at a rate of 2-4°C / min, keeping warm for 60-90min, turning the crucible 5-6 times within 1 minute, keeping warm for 30-40min, taking it out and turning it over, repeating the second stage operation 3-5 times, and continuing to keep warm for 1-2h; the third stage: cooling to 900-950°C at a rate of 7-10°C / min, and keeping warm for 30-60min.
[0013] It is further defined that the homogenization temperature in S3 is 600-630° C. and the time is 24-48 hours.
[0014] It is further defined that the hot extrusion temperature in S4 is 550-600°C, the extrusion ratio is 25:1, and the extrusion rate is 0.3-0.5 mm / s.
[0015] It is further defined that the deformation of a single cold rolling pass in S4 is 4-8%, the cold rolling rate is 8-10 mm / s, the total cold rolling deformation is 10-25%, and intermediate annealing is performed at 600-630°C for 30-60 minutes every two passes.
[0016] It is further defined that the cyclic heat treatment temperature in S4 is 660-690°C, the time is 30-60 minutes, and then it is taken out and air-cooled.
[0017] It is further defined that the cyclic heat treatment is cycled 5 to 10 times.
[0018] The second object of the present invention is to provide a superelastic Mg-Sc-Gd shape memory alloy prepared according to the above method, wherein the alloy has superelasticity in the range of -120°C to 50°C.
[0019] The third object of the present invention is to provide a superelastic Mg-Sc-Gd shape memory alloy prepared by the above method for application in the fields of aerospace, biomedicine, artificial intelligence and automotive engineering.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] The present invention adopts a high-temperature closed smelting method to prepare a Mg-Sc based alloy with uniform composition, and achieves the purpose of maximizing the strength of the alloy while reducing the cost by strictly controlling the doping amount of the low-cost rare earth element Gd. At the same time, the superelasticity and mechanical properties of the Mg-Sc based memory alloy are comprehensively improved by combining hot extrusion, cold rolling and cyclic heat treatment methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram of the structure of a 316 stainless steel high-temperature closed melting crucible used in the preparation method of the present invention;
[0023] Figure 2 The actual object and element distribution diagram of the cast Mg-19.1at%Sc alloy in Comparative Example 1; wherein (a) is the actual object photo, and (b) is the element distribution;
[0024] Figure 3 The metallographic and mechanical properties diagram of the homogenized Mg-19.1at%Sc alloy after solid solution treatment in Comparative Example 1; (a) - metallographic photo, (b) - mechanical properties;
[0025] Figure 4 EBSD results of the Mg-19.1at%Sc alloy in Comparative Example 1 and its superelastic performance diagram at different temperatures; (a)-EBSD, (b)-superelasticity;
[0026] Figure 5 The actual object and element distribution diagram of the cast Mg-17.8at%Sc-1.3at%Gd alloy in Example 1; wherein (a) is the actual object photo, and (b) is the element distribution;
[0027] Figure 6 XRD patterns of Mg-17.8at%Sc-1.3at%Gd alloys after solution treatment at different temperatures;
[0028] Figure 7The metallographic and mechanical properties diagram of the Mg-17.8at%Sc-1.3at%Gd alloy after homogenization treatment in Example 1; wherein (a) - metallographic photo, (b) - mechanical properties;
[0029] Figure 8 This is a physical picture of the hot-rolled Mg-17.8at%Sc-1.3at%Gd alloy in Comparative Example 2;
[0030] Fig. 9 This is a graph of superelastic properties of Mg-17.8at%Sc-1.3at%Gd alloy at -120°C in Comparative Example 3;
[0031] Fig.10 EBSD results of the Mg-17.8at%Sc-1.3at%Gd alloy in Example 1 and its superelastic performance diagram at different temperatures; (a)-EBSD, (b)-superelasticity;
[0032] Fig.11 This is a diagram of the superelastic performance of the Mg-17.8at%Sc-1.3at%Gd alloy in Comparative Example 4 at different temperatures; (a) represents superelasticity at -120°C, and (b) represents superelasticity at different temperatures. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0035] Embodiment 1, combination Figure 1 The preparation method of the superelastic Mg-Sc based shape memory alloy of this embodiment is carried out according to the following steps:
[0036] (1) Pure magnesium (purity 99.99%) and Mg-6.3at%.Gd master alloy (purity 99.99%) were cut into block-shaped rectangular blocks with a length of 40 mm, a width of 13 mm, and a height of 12 mm. The surface oxide scale was polished off using 200# coarse sandpaper, and the blocks were ultrasonically cleaned in alcohol for 5 minutes, and then taken out and dried with cold air. Block-shaped pure scandium (purity 99.99%) was cut into strips with a length of 5 mm and a width of 2 mm, and the blocks were ultrasonically cleaned in alcohol for 5 minutes, and then taken out and dried with cold air. The corresponding masses of pure magnesium, scandium strips, and Mg-6.3at%.Gd master alloy were weighed according to the atomic percentage of Mg-17.8at%Sc-1.3at%Gd.
[0037] (2) This embodiment uses a 316 stainless steel crucible, and the schematic diagram of the crucible structure is as follows: Figure 1 As shown. The upper cover and the lower cover are sealed and connected to the crucible wall by welding. The thickness of the upper cover / lower cover is twice the wall thickness. θ is 85°, H = 6d, and the diameter Φ 5 1 / 4*Φ 3 , the height of the bolt is h = 2*d. The stainless steel crucible and the bolt are placed in a muffle furnace for heat treatment at 850℃ for 30min, and then quenched. The inside of the crucible and the bolt after quenching are soaked and cleaned with 1.8wt.% dilute sulfuric acid for 24h to remove the surface oxide scale and oil stains, and then rinsed with alcohol and placed in an oven and dried at 150℃ to ensure that the inside of the crucible and the bolt are completely dried without any moisture residue.
[0038] (3) Put the metal and alloy raw materials into the crucible from the feeding port at the top of the crucible. In order to ensure the uniform distribution of the Sc element during the smelting process, 1 / 3 pure magnesium is placed at the bottom of the crucible, followed by 1 / 3 scandium bar, 1 / 2Mg-6.3at%.Gd master alloy, 1 / 3 scandium bar, 1 / 3 pure magnesium, 1 / 3 scandium bar, 1 / 2Mg-6.3at%.Gd master alloy, and finally 1 / 3 pure magnesium is placed on the top. Then, a mixed gas of sulfur hexafluoride and carbon dioxide (content of 6vol.%:94vol.%) is introduced from the feeding port at the top of the crucible, with a gas flow rate of 1.0mL / min, to remove the air inside the crucible. Since the density of the mixed gas is higher than that of air, when the mixed gas has completely exhausted the air inside the crucible, the ventilation steel pipe is immediately pulled out, the bolts are tightened, and the connection between the bolts and the crucible is welded to complete the sealing of the crucible, thereby ensuring that only the mixed gas exists inside the crucible.
[0039] (4) The crucible is placed in a high-temperature furnace, and the smelting is divided into three stages: ① In the first stage, the high-temperature furnace is heated to 850°C at a heating rate of 15°C / min and kept warm for 60 minutes; ② In the second stage, the temperature is raised to 1050°C at a heating rate of 4°C / min, and the crucible is clamped out after being kept warm for 60 minutes, and the molten alloy liquid inside the crucible is fully mixed. The crucible is then placed back in the 1050°C high-temperature furnace and kept warm for 30 minutes, and then taken out and turned over. After repeating step ② 3 times, the crucible is placed in the 1050°C high-temperature furnace and kept warm for 2 hours; ③ In the third stage, the temperature is lowered to 900°C at a rate of 7°C / min, and after being kept warm for 30 minutes, the crucible is taken out, the bottom of the crucible is first contacted with the water surface in the water tank, and the crucible is slowly sunk into the water tank at a rate of 1 mm / s. After being completely immersed in the water tank and kept for 6 minutes, the crucible is taken out, and the upper cover is turned off by a lathe, and the ingot can be taken out to complete the smelting.
[0040] (5) The Mg-17.8at.%Sc-1.3at.%Gd alloy ingot was kept at 600°C for 24 hours for homogenization treatment.
[0041] (6) A disc with a diameter of 59 mm and a thickness of 11 mm was cut from the homogenized Mg-17.8at.%Sc-1.3at.%Gd alloy ingot for hot extrusion experiment. Before extrusion, the alloy and the extrusion die were heated to 550°C in a resistance furnace and kept warm for 120 minutes. Then, hot extrusion deformation was performed at an extrusion ratio of 25:1 and an extrusion rate of 0.5 mm / s. The alloy after hot extrusion was then cold rolled. The deformation of each pass was 5% during cold rolling. The cold rolling rate was 10 mm / s. Intermediate annealing was performed at 600°C for 30 minutes every two passes. The total cold rolling deformation was 15%. After cold rolling deformation, the alloy was subjected to cyclic heat treatment, that is, heat treatment at 690°C for 30 minutes, then taken out for air cooling, and the cycle treatment was repeated 10 times.
[0042] Comparative Example 1: Mg-19.1at.%Sc binary alloy
[0043] The difference between this comparative example and Example 1 is that:
[0044] In step (1): pure magnesium and scandium bars of corresponding mass are weighed according to the atomic percentage of Mg-19.1at%Sc to prepare a Mg-19.1at.%Sc binary alloy.
[0045] In step (3): the raw materials are placed in the following order: 1 / 3 pure magnesium is placed at the bottom, followed by 1 / 3 scandium bars, 1 / 3 pure magnesium, 1 / 3 scandium bars, 1 / 3 pure magnesium, and 1 / 3 scandium bars.
[0046] In step (6), the Mg-19.1at.%Sc binary alloy after homogenization is subjected to hot rolling deformation, the hot rolling temperature is 660°C, the total deformation is 85%, the deformation per pass is 8%, and the hot rolling rate is 1 m / s. The alloy is then subjected to cyclic heat treatment, that is, heat treatment at 690°C for 30 minutes, then air cooling, the cycle treatment is repeated 10 times, and finally heat treatment at 690°C for 30 minutes is performed before quenching.
[0047] The other steps and parameters are the same as those in Example 1.
[0048] Comparative Example 2:
[0049] The difference between this comparative example and Example 1 is that:
[0050] In step (6), the Mg-17.8at%Sc-1.3at%Gd alloy after homogenization is subjected to hot rolling deformation, the hot rolling temperature is 660°C, the total deformation is 85%, the deformation per pass is 8%, and the hot rolling rate is 1 m / s. The alloy is then subjected to cyclic heat treatment, that is, heat treatment at 690°C for 30 minutes, then air cooling, cyclic treatment 10 times, and finally heat treatment at 690°C for 30 minutes before quenching.
[0051] The other steps and parameters are the same as those in Example 1.
[0052] Comparative Example 3:
[0053] The difference between this comparative example and Example 1 is that in step (6), cold rolling is omitted and only hot extrusion and cyclic heat treatment are performed. The other steps and parameters are the same as those in Example 1.
[0054] Comparative Example 4:
[0055] The difference between this comparative example and Example 1 is that in step (6), the total cold rolling deformation is 30%. The other steps and parameters are the same as those in Example 1.
[0056] Figure 2 Figure 3 shows the physical object and element distribution of the cast Mg-19.1at%Sc alloy. The alloy smelted in a closed high-temperature furnace has a low degree of surface oxidation and a more uniform distribution of Mg and Sc elements.
[0057] The Mg-19.1at%Sc alloy after homogenization treatment in Comparative Example 1 was solution treated at 690°C for 30 minutes. Then the metallographic structure and mechanical properties were tested. The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that the metallographic results show that the grain morphology of the alloy is equiaxed, with an average grain size of ~100μm; the compressive stress-strain curve shows that the compressive yield strength σ sIt is about 200MPa, and does not show the typical double yield phenomenon of shape memory alloys, indicating that the alloy that has only undergone solid solution treatment does not have shape memory effect or superelasticity.
[0058] Figure 4 These are the EBSD results of the Mg-19.1at%Sc alloy after hot rolling and cyclic heat treatment, and the superelastic performance diagram at different temperatures. The results show that the average grain size of the alloy is about 163μm, and it has superelasticity in the temperature range of -120℃ to -20℃, but the superelastic performance is poor and there is a large residual strain (about 1%).
[0059] Figure 5 This is the physical object and element distribution diagram of the cast Mg-17.8at%Sc-1.3at%Gd alloy. Similar to the Mg-19.1at%Sc binary alloy, the surface oxidation degree is low and the distribution of Mg, Sc and Gd elements is relatively uniform.
[0060] The Mg-17.8at%Sc-1.3at%Gd alloy after homogenization treatment in Example 1 was solution treated at 540℃, 600℃, 660℃ and 690℃ for 30min respectively. Then XRD test was performed. The results are as follows: Figure 6 As shown, it can be seen that the β single phase is obtained by solution treatment at 690°C.
[0061] The Mg-17.8at%Sc-1.3at%Gd alloy after homogenization treatment in Example 1 was subjected to solution treatment at 690°C for 30 minutes. The metallographic structure and mechanical properties were then tested. Figure 7 As shown, from Figure 7 It can be seen that the metallographic results show that the alloy grains are also equiaxed, with an average grain size of about 50 μm, which is smaller than the Mg-19.1at.%Sc binary alloy; the yield strength σ s The value is 292MPa, which is higher than that of Mg-19.1at.%Sc alloy, indicating that the strength of 1Mg-Sc alloy is improved. The increase in strength may be due to grain refinement and solid solution strengthening. However, the typical double yield phenomenon of shape memory alloy is not shown, indicating that the alloy does not have shape memory effect or superelasticity.
[0062] Figure 8 This is a photo of the hot-rolled Mg-17.8at%Sc-1.3at%Gd alloy. After the same hot-rolling process, after adding the third component Gd, the processing performance of the alloy deteriorates, and hot rolling is not suitable as a thermal deformation process.
[0063] Fig. 9This is a diagram of the superelastic properties of Mg-17.8at%Sc-1.3at%Gd alloy at -120°C after hot extrusion combined with cyclic heat treatment. Although the alloy has superelasticity at -120°C, its mechanical properties are poor and its superelastic properties are also poor.
[0064] Fig.10 The EBSD results of the Mg-17.8at%Sc-1.3at%Gd alloy after hot extrusion, total cold rolling deformation (Example 1) and cyclic heat treatment and the superelastic performance diagram at different temperatures, the average grain size of the alloy is about 50μm, which is smaller than that of the Mg-19.1at%Sc alloy, and it has superelasticity in a wide temperature range of -120℃ to 50℃, and the temperature range is 70℃ higher than that of the Mg-19.1at%Sc alloy; and the superelastic performance is improved, the residual strain is reduced, and complete superelasticity with zero residual strain is obtained at -120℃.
[0065] Fig.11 Figure 2 is a graph of the superelastic properties of Mg-17.8at%Sc-1.3at%Gd alloy at different temperatures after hot extrusion, total cold rolling deformation (Comparative Example 7) and cyclic heat treatment. The superelasticity at -120°C is better than that of Mg-19.1at%Sc alloy, but Fig.10 The superelastic properties are poor and the mechanical properties are poor.
[0066] Therefore, the superelastic properties of Mg-Sc alloy can be improved by adding the third component Gd in combination with specific deformation and post-deformation heat treatment.
[0067] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a superelastic Mg-Sc based shape memory alloy, the method being carried out according to the following steps: S1: According to Mg-xat.%Sc-yat.%Gd, x=17-22, y=1-2, weigh pure magnesium, pure scandium and Mg-Gd master alloy; S2: Put the raw materials into a stainless steel crucible in order, introduce a mixed gas of SF6 and CO2 to remove the air in the crucible, and then melt them in stages under high temperature and closed conditions, and obtain an ingot after cooling; S3: homogenizing the ingot; S4: After homogenization treatment, the ingot is first hot extruded, then cold rolled, and finally cyclically heat treated to obtain a superelastic Mg-Sc based shape memory alloy.
2. The method according to claim 1, characterized in that The raw materials in the S2 crucible are, from the bottom to the top, 1 / 3 pure magnesium, 1 / 3 pure scandium, 1 / 2 intermediate alloy, 1 / 3 pure scandium, 1 / 3 pure magnesium, 1 / 3 pure scandium, 1 / 2 intermediate alloy, and 1 / 3 pure magnesium.
3. The method according to claim 1, characterized in that: The smelting in S2 is divided into three stages: the first stage: heating to 800-850°C at a rate of 15-20°C / min, and keeping warm for 60-90min; the second stage: heating to 1000-1050°C at a rate of 2-4°C / min, keeping warm for 60-90min, turning the crucible 5-6 times within 1 minute, keeping warm for 30-40min, taking it out and turning it over, repeating the second stage operation 3-5 times, and continuing to keep warm for 1-2h; the third stage: cooling to 900-950°C at a rate of 7-10°C / min, and keeping warm for 30-60min.
4. The method according to claim 1, characterized in that The homogenization temperature in S3 is 600-630°C and the time is 24-48h.
5. The method according to claim 1, characterized in that In S4, the hot extrusion temperature is 550-600°C, the extrusion ratio is 25:1, and the extrusion rate is 0.3-0.5 mm / s.
6. The method according to claim 1, characterized in that In S4, the deformation of a single cold rolling pass is 4-8%, the cold rolling rate is 8-10 mm / s, the total cold rolling deformation is 10-25%, and intermediate annealing is performed at 600-630°C for 30-60 minutes every two passes.
7. The method according to claim 1, characterized in that In S4, the cycle heat treatment temperature is 660-690°C, the time is 30-60 minutes, and then it is taken out and air-cooled.
8. The method according to claim 7, characterized in that The cyclic heat treatment is repeated 5 to 10 times.
9. The superelastic Mg-Sc-Gd shape memory alloy prepared by the method according to any one of claims 1 to 8, characterized in that: The alloy has superelasticity in the range of -120°C to 50°C.
10. Application of the superelastic Mg-Sc-Gd shape memory alloy according to claim 9 in the fields of aerospace, biomedicine, artificial intelligence and automotive engineering.
Citation Information
Patent Citations
Magnesium alloy that exhibits superelastic effect and / or shape-memory effect
CN108603254A
Mg-Sc-X alloy under the action of ultrahigh pressure and a preparation method thereof
CN110747382A
Design method for preparing high-concentration and high-performance magnesium alloy based on Mg-Gd-Y and magnesium alloy
CN115161504A
Mg-Sc-based light shape memory alloy and obtaining method thereof
CN118064776A
Pseudoelastic magnesium alloy, pseudoelastic magnesium alloy component, and production method thereof
US20150064053A1
